If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 1)(5x) = 0 Reorder the terms: (1 + 2x)(5x) = 0 Remove parenthesis around (5x) (1 + 2x) * 5x = 0 Reorder the terms for easier multiplication: 5x(1 + 2x) = 0 (1 * 5x + 2x * 5x) = 0 (5x + 10x2) = 0 Solving 5x + 10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(1 + 2x) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(1 + 2x)' equal to zero and attempt to solve: Simplifying 1 + 2x = 0 Solving 1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 0 + -1 2x = 0 + -1 Combine like terms: 0 + -1 = -1 2x = -1 Divide each side by '2'. x = -0.5 Simplifying x = -0.5Solution
x = {0, -0.5}
| -0.90(30)+188=y | | 3.5x=.5x | | 4+2n-1=8n+11-5n | | v=-15+u | | 4p^2+16p-20=0 | | -0.90(20)+188=y | | 3(x+-6)=-21 | | 2cosx-5cosx-4=0 | | y=2xsquared-4x | | -0.2x+7.12=-0.4x+1.32 | | 186=6(7+6v) | | 7x-14y=-56 | | 18+4(t-9)=6 | | 8x-10=3x-5 | | 3(x+1.89)=2x | | 3.3x-24=1.8x+9 | | -5.8v-44.2=-8.3v | | T^2-10t=24 | | 2.1=3x+4.8 | | R+2r-3r= | | 9.5x+5-8.5x=4 | | -9(1+x)=-9(x-6) | | .2x+2=18 | | 9x-46.4=x | | T^2-10=24 | | 15a-20=100 | | 8r-16+6=2r+2 | | 2(c-7)= | | RI^2-EI+P=0 | | 1.4x-3.8=0.6x-1.56 | | (2a^2-72)/(4a-24) | | 2x^3+x^2+28=0 |